2017
DOI: 10.1111/ctr.12882
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term health‐related quality of life in living liver donors: A south Asian experience

Abstract: Living donor hepatectomy is safe with acceptable morbidity and excellent long-term HRQOL with no change in career path or significant alteration of lifestyle for donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…7780 Nevertheless, bereaved donors almost universally state that they take comfort in having done all they could and they have no regrets about having donated. 13,14,20,77,78 Additionally, we previously reported very low average levels of perceived guilt or responsibility for the recipient’s death in our cohort, 14 and other liver donor follow-up studies have not found recipient death to increase risk for adverse long-term general HRQOL. 18,20,21 Moreover, the experience of grief following bereavement does not necessarily mean that an individual will meet criteria for a psychiatric disorder, including the conditions we assessed; in fact, a large empirical literature shows that the vast majority of bereaved individuals do not develop any psychiatric disorder.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…7780 Nevertheless, bereaved donors almost universally state that they take comfort in having done all they could and they have no regrets about having donated. 13,14,20,77,78 Additionally, we previously reported very low average levels of perceived guilt or responsibility for the recipient’s death in our cohort, 14 and other liver donor follow-up studies have not found recipient death to increase risk for adverse long-term general HRQOL. 18,20,21 Moreover, the experience of grief following bereavement does not necessarily mean that an individual will meet criteria for a psychiatric disorder, including the conditions we assessed; in fact, a large empirical literature shows that the vast majority of bereaved individuals do not develop any psychiatric disorder.…”
Section: Discussionsupporting
confidence: 54%
“…First, studies of these long-term psychosocial outcomes have been predominantly cross-sectional 1222 and, as such, have been unable to examine trends over time. Second, most reports do not examine clinically significant difficulties in the psychosocial domains assessed, and instead focus on either nonspecific, generic HRQOL assessments 13,21,23 or unvalidated, single-item assessments with unknown performance characteristics. 12,1520 Third, the clear majority of reports examine small single-site cohorts, 12,13,1520,22 resulting in findings of unknown, potentially limited, generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…[5,10,25,36,37] In addition, several reports have shown that the HRQoL in donors is, on average, above the normative levels in the long term. [5,15,16,24,25,[44][45][46] A multicenter prospective study showed that the HRQoL of living liver donors was not negatively affected by donation up to 11 years after liver transplant. [5] Our results support the findings published in these studies; however, in our study, we compared liver donors with potential donors rather than with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5,10,25,36,37 ] In addition, several reports have shown that the HRQoL in donors is, on average, above the normative levels in the long term. [ 5,15,16,24,25,44–46 ] A multicenter prospective study showed that the HRQoL of living liver donors was not negatively affected by donation up to 11 years after liver transplant. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%